A Structural Investigation of T’-Pr2-xCexCuO4 nanocrystals with x = 0.13: Putu Eka Dharma Putra, I Gede Arjana, Budi Haryanto, Resky Irfanita, Malik Anjelh Baqiya, Darminto Darminto - Putu Eka Dharma Putra Putu Eka Dharma Putra; I Gede Arjana I Gede Arjana; Budi Hariyanto Budi Hariyanto; Resky Irfanita Resky Irfanita; Malik Anjelh Baqiya Malik Anjelh Baqiya; Darminto Darminto (Jurnal Fisika dan Aplikasinya, 2021)
This report is briefly investigating the structural defect information of T’-Pr2-xCexCuO4 (T’-PCCO) nanocrystals with x = 0.13 at three different calcination temperatures. The as-synthesized powder of Pr2-xCexCuO4 (PCCO) nanocrystals with x = 0.13 were synthesized by using the chemically dissolved method within three different calcination temperatures, namely 900oC, 950oC, and 1000oC for 15 h in air. X-ray diffraction (XRD) technique is used to characterize the phase, structural, and crystalline defect information on the nanocrystal powder. It is found that all the indexed peaks are confirmed as PCCO phase with space group of I4/mmm and a minor impurity of Fm-3m space group. The lattice parameters are confirmed to be fluctuated signifying the stability of the Coulomb force at those temperatures. The post-Rietveld analysis using Bond Valance Sum (BVS) calculation shows the Ce-dependent of T’-PCCO nanocrystals while the Fourier difference suggests that the created crystalline defect as a part of the tetravalent doping effect which binds stronger apical oxygen. Moreover, at Pr- and Cu-site, the scattering distribution are fluctuating with the stable structure at 1000oC. This initial structural information is worth complementing the fundamental feature for understanding the T’-type cuprates.